-168-x=53+12x

Simple and best practice solution for -168-x=53+12x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -168-x=53+12x equation:


Simplifying
-168 + -1x = 53 + 12x

Solving
-168 + -1x = 53 + 12x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-12x' to each side of the equation.
-168 + -1x + -12x = 53 + 12x + -12x

Combine like terms: -1x + -12x = -13x
-168 + -13x = 53 + 12x + -12x

Combine like terms: 12x + -12x = 0
-168 + -13x = 53 + 0
-168 + -13x = 53

Add '168' to each side of the equation.
-168 + 168 + -13x = 53 + 168

Combine like terms: -168 + 168 = 0
0 + -13x = 53 + 168
-13x = 53 + 168

Combine like terms: 53 + 168 = 221
-13x = 221

Divide each side by '-13'.
x = -17

Simplifying
x = -17

See similar equations:

| 18x^2+18x-24=0 | | 4(5x+10)=4(x-6) | | 12x^2-204x+630=0 | | 7x-36=48+11x | | 7+n-2=-5-n | | -16-12x=40-8x | | p+2=-2-3p | | -4p+7=7-4p | | x-77=35-6 | | 2X^2-34X+105=0 | | 0=2m+5m | | 11x-6=-39 | | 15=m-4m | | p-5-3=-9 | | 3x-7+x=10 | | -12=-5b-b | | 2(x+1)-4=5x-3(2+x) | | 7x-114=40-4x | | 9x-5x+3x-x+16=22 | | 42=28-12x | | (x^2)+6=8x | | -63-4x=135+7x | | 8=4-3b+1 | | 500+35*X=55*x | | -4n+2(-7n-5)=-7n+1 | | y^2=-4x^2+8x-3 | | X+36x=130 | | (x^2)-6x=1 | | -39-6b=-5(b+8) | | (4w^2)+12w+9=49 | | 3x=11x+25 | | -9cosx-3sinx=0 |

Equations solver categories